Charles Miller Fisher: the 65th anniversary of the publication of his groundbreaking study “Transient Monocular Blindness Associated with Hemiplegia” - Araújo, Tiago Fernando Souza de; Lange, Marcos; Zétola, Viviane H.; Massaro, Ayrton; Teive, Hélio A. G. (Arquivos de Neuro-Psiquiatria, 2017)
Charles Miller Fisher is considered the father of modern vascular neurology and one of the giants of neurology in the 20th century. This historical review emphasizes Prof. Fisher's magnificent contribution to vascular neurology and celebrates the 65th anniversary of the publication of his groundbreaking study, “Transient Monocular Blindness Associated with Hemiplegia.”
Keywords: transient ischemic attack; amaurosis fugax; hemiplegia